Fabrication and photosensitivity of CdS photoresistor on silica nanopillars substrate. (December 2016) - Liu, Jing; Liang, Yaxiang; Wang, Lin; Wang, Bo; Zhang, Tianchong; Yi, Futing
Abstract: Silica nanopillars are used as substrate for Cadmium sulfide (CdS) photoresistor for the first time. The nanopillars substrate with the large surface ratio can increase the quantity of sensitive material and the surface of light response, which can improve the photosensitivity of the CdS photoresistor obviously. Silicon nanopillars are fabricated by Cesium Chloride (CsCl) self-assembly lithography and inductively coupled plasma (ICP) dry etching, after oxidation, the silicon nanopillars changes to silica nanopillars totally, then the 200 nm thickness CdS film is deposited on the nanopillars surface by RF magnetron sputtering using CdS ceramic target. XRD patterns of the nanopillar and planar substrates after CdS film covering indicate that all the deposited films are crystal. Photosensitivity properties of the photoresistor are tested by a home-made instrument in our group. The test results show that the nanopillar based photoresistor has the higher photosensitivity response than the planar one with different irradiance from 400 to 11, 000 μW/cm 2 . With 10, 000 μW/cm 2 irradiance at the room temperature, the photosensitivity response for the planar sample is only 62, while the response for the nanopillar sample achieves to 137, which is more than double of the planar one. The result reveals that the nanopillars morphology can be used as substrate to increase the property of the photoresistor.